2016
DOI: 10.1002/jip.1463
|View full text |Cite
|
Sign up to set email alerts
|

Police officers' use of evidence to elicit admissions in a fictitious criminal case

Abstract: We examined how police officers planned to interview suspects in a situation where they lacked information about a critical phase of a crime (i.e., the time during which the crime took place) but possessed information about less critical phases of the crime (i.e., the time before and/or after the crime took place). The main focus was the officers' planned use of the available information (evidence) to elicit admissions about the critical phase. A survey was distributed to police officers (n = 69) containing a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…The questions were kept broad to understand how officers use inconsistency types in general. Moreover, the findings concur with previous studies investigating police officers' perceptions of statement inconsistency in other countries (Alison, 2005;Greuel, 1992;Tekin et al, 2017) as well as with experimental studies examining statement inconsistency (Granhag, Rangmar, & Strömwall, 2015;Mac Giolla & Granhag, 2015), which support the validity of police officers' reports in this study.…”
Section: Methodological Considerationssupporting
confidence: 92%
See 1 more Smart Citation
“…The questions were kept broad to understand how officers use inconsistency types in general. Moreover, the findings concur with previous studies investigating police officers' perceptions of statement inconsistency in other countries (Alison, 2005;Greuel, 1992;Tekin et al, 2017) as well as with experimental studies examining statement inconsistency (Granhag, Rangmar, & Strömwall, 2015;Mac Giolla & Granhag, 2015), which support the validity of police officers' reports in this study.…”
Section: Methodological Considerationssupporting
confidence: 92%
“…Officers were asked whether they thought that liars who are presented with incriminating evidence, after explanations for it have been exhausted, would be more likely to change their statement to fit it with the evidence or to maintain their statement, risking statement-evidence inconsistency. Previous research has found that police officers in several countries tend to employ the SUE technique in investigative interviews (Tekin, Granhag, Strömwall, & Vrij, 2017). The application of this technique is more likely to elicit statement-evidence inconsistency than within-statement inconsistency in liars’ statements (Granhag et al, 2013; Tekin, Granhag, Strömwall, & Vrij, 2016).…”
Section: The Current Studymentioning
confidence: 99%
“…However, the findings of the current study are only generalizable to situations whereby pairs of suspects claim to have been together at the time the crime took place. The model statement should be used alongside other strategies found to gather information and increase cues to deceit (e.g., the Strategic Use of Evidence; Tekin et al ., ; Tekin, Granhag, Strömwall, & Vrij, ). After all, the more strategies we have in place to increase information gathering and elicit cues to deceit, the more likely we are to accurately differentiate between truthful and lying suspects.…”
Section: Discussionmentioning
confidence: 99%